What do aircraft accident investigators do and what makes them good at it? Developing a competency framework for investigators using grounded theory - Nixon, Jim; Braithwaite, Graham R. (Elsevier, 2017)
We present a new analysis of the tasks carried out by air accident investigators and propose a new competency framework which captures the competencies demanded of an effective investigator. Using a subject-matter expert panel, a hierarchical task analysis (HTA) was developed to frame and organise the diverse activities that are required of the air accident investigator. Supported by the HTA, a competency framework was developed using structured interviews based on repertory-grid interview technique. Grounded theory was used to abstract competencies derived from the interviews. The resultant competency framework could be applied to selection and training future investigators in other safety critical domains. More immediately, the framework can deliver insight into what differentiates the good investigator from the excellent investigator.
Keywords: Air accident investigator; Competency framework; Repertory grid; Grounded theory